Examining the Link Between Physical Activity and Cognitive Function: A Parallel Mediation Model of Health and Wellbeing Among Adolescents - Luan, Xi; Liu, Ji; Luo, Xin (Frontiers in Psychology, 2022)
Background: Adolescents’ engagement in daily physical activity brings multiple benefits, including reduction in obesity, improvement of mental health, and enhancement of cognitive function. While prior studies have examined the link between physical activity and cognitive function, little is known regarding the extent to which this relationship is shaped by health and wellbeing factors. Methods: This study examines how subjective wellbeing and general health mediate the relationship between adolescents’ physical activity and cognitive function, by estimating a parallel structural equation model (SEM) using the newly-released Program for International Student Assessment (PISA) 2018 dataset. Specifically, a total of 63,228 15-year-old subjects in 9 economies satisfied the study inclusion criteria. Frequency of moderate physical activity (MPA, ≥ 3.0 MET) was reported weekly; subjective wellbeing and general health were assessed using an internationally validated multi-item standardized questionnaire; cognitive function was modelled as a latent function consisting of 10 plausible values in reading, mathematics, and science achievement tests. Results: Findings indicated that increase in weekly MPA was positively associated with higher levels of subjective wellbeing (p<.001), general health (p<.001), and cognitive function (p<.001) among the study subjects. Parallel mediation analyses revealed that while more frequent weekly MPA had relatively large direct effects (p<.001) on cognitive function, its indirect effects channeling through improvements in subjective wellbeing and general health were non-trivial (p<.001). Heterogeneity results showed that boosts to cognitive function associated with more frequent physical activity were larger for mathematics and science than for reading (p<.001). Conclusion: This study used a large-scale international dataset to show that the positive relationship observed between physical activity and cognitive function among adolescents was robust, and that subjective wellbeing and general health were two critical mediators through which physical activity positively affected cognitive function.